Treatment Adherence to Injectable Treatments in Pediatric Growth Hormone Deficiency Compared With Injectable Treatments in Other Chronic Pediatric Conditions: A Systematic Literature Review - Gomez, Roy; Ahmed, S. Faisal; Maghnie, Mohamad; Li, Dejun; Tanaka, Toshiaki; Miller, Bradley S. (Frontiers in Endocrinology, 2022)
Background: Pediatric patients with growth hormone deficiency (GHD) are currently treated with daily injections of recombinant human growth hormone (rhGH) to promote linear growth and enable attainment of normal adult height. One of the main reasons for suboptimal growth during rhGH therapy is non-adherence to treatment. The objective of this systematic literature review was to examine the recent literature on pediatric adherence to injectable treatments for chronic conditions (focusing on rhGH) to characterize levels of adherence and identify the factors/barriers associated with adherence. Methods: The Embase and MEDLINE databases (January 2015–October 2020) were searched to identify publications describing studies of pediatric patients (aged ≤17 years) with GHD and other chronic conditions requiring daily or weekly injectable treatments; a similar targeted search of Chinese literature was also performed. Adherence data were extracted from the included studies and summarized. Risk of bias was determined using the Cochrane Risk of Bias tool 2 or the Newcastle-Ottawa Scale. Results: A total of 23 publications were included, with all publications except for one (multiple sclerosis) focused on pediatric GHD studies: there were two clinical trials, 18 observational studies and three survey studies. Study sample sizes ranged from 30 to 13,553 patients (median: 95 patients). The definition of adherence varied between studies and included mean adherence rate, median adherence rate, and the percentage of patients within pre-specified adherence categories. Of the publications assessing adherence to daily rhGH, 11 studies reported 12-month mean adherence rate (range: 73.3%– 95.3%) and 8 studies reported median adherence (range: 91%– 99.2%). The barriers to treatment adherence identified included self-administration, increased administration frequency, age (adolescence), longer treatment duration, device design, and insufficient family education, awareness, and/or engagement. Recommendations for increasing adherence included using adherence reminder tools, increasing patient engagement/education, and improving injection device design and drug product. Conclusions: Adherence to rhGH treatment was high (>80%) for many studies, though comparability between studies was limited given the substantial heterogeneity in the way adherence was defined, measured, and reported. To address this heterogeneity, we recommend standardizing how adherence is defined and reported and encourage the use of standardized study designs and outcome measures.